Impact of BTV-3 Circulation in Belgium in 2024 and Current Knowledge Gaps Hindering an Evidence-Based Control Program - Virginie Van Leeuw; Ilse De Leeuw; Nicolas Degives; Pieter Depoorter; Jeroen Dewulf; Jean-Baptiste Hanon; Jozef Hooyberghs; Annick Linden; Laura Praet; Marc Raemaekers; Claude Saegerman; Xavier Simons; et al. (Viruses)
Between 2006 and 2010, northwestern Europe experienced its first significant bluetongue virus (BTV) outbreak, driven by the spread of BTV-8, which had major repercussions on the European livestock sector. While BTV-3 was first identified in Europe in Italy in 2017, a new introduction of the virus was reported in 2023, in the Netherlands, and subsequently spread rapidly across the continent. A limited number of BTV-3 outbreaks were notified in Belgium in 2023, leading to the loss of its BTV-free status. In the following year, 2024, the virus spread throughout the country in a short time period. This study describes the impact of BTV-3 circulation in Belgium in 2024, detailing both its geographic spread and the associated increase in mortality, reduced births recorded, and decline in milk production among ruminants. Furthermore, preliminary results on the effectiveness of field vaccination and maternal immunity transfer are presented, as well as critical gaps that hinder the development of a robust, evidence-based management strategy. As the epidemiological situation is expected to become more complex in the future, due to the co-circulation of multiple BTV serotypes and other Culicoides-borne diseases, such as EHDV, effective collaboration and communication among stakeholders and international authorities will be crucial for implementing measures to mitigate the spread of these diseases.